The Role of Peer Counseling on Mental Health - Salsabila Salsabila; Jessica Wiryantara; Nurnadiah Salsabila; Muhammad Afif Alhad (Department of Guidance and Counseling, FIP, Undiksha, 2020)
Adolescence is identical with the phase of searching for identity. Therefore, adolescents solve their own problems and have difficulty communicating because parents find it difficult to understand the desires of their teenage children and are frustrated dealing with them so counselors are needed to bridge the communication between parents and adolescents. This type of research is a descriptive study using explanatory research. Respondents used were good teens aged 18 years to 22 years. The purpose of the study was to examine the effect of Peer Counseling (X) and Mental Health (Y). Data were tested by multiple regression analysis using SPSS v 16.00 for Windows. The results of the analysis prove that the variable Peer Counseling gives an influence on mental health as indicated by the calculated F value of 38,709 with a significance value of 0.00 (or <0.05). Prearson correlation coefficient value is 0.668 or 66.8% which means a high level of influence between peer counseling and mental health variables.